Challenges in Tunneling in the Himalayas: A Survey of Several Prominent Excavation Projects in the Himalayan Mountain Range of South Asia - Diwakar KC; Kabindra Gautam; Harish Dangi; Sushma Kadel; Liangbo Hu (Geotechnics, 2022)
The Himalayas are one of the most unstable regions in the world. Underground excavations are very challenging in this region due to the fragile geology, tectonic activities and complex geological structures. In the present study, three hydropower head race tunnel projects from Nepal, as well as six additional tunnel projects from Bhutan, India and Pakistan located at different parts of the Himalayas, are reviewed with a focus on the common problems encountered during the tunneling and their possible causes and remedies. It is found that rock bursts often occurred around the overburden of 1000 m or higher, while tunnel squeezing problems were commonly observed in a wide range of overburden. Most of the rock failures occurred in sheared zones, thrusts and heavily weathered rock mass. The geological conditions around these projects are often characterized by significant presence of folds, faults, joints and interbedding of different types of rock strata; they are so complex and diverse that it is often difficult to accurately predict the field condition from conventional geotechnical site investigation. In many cases, the presence of shear zones, thrusts and tectonic activities has a strong influence on the in situ stress. Review of these prominent projects suggests that the complicated dynamics between a wide range of geological and geotechnical factors play a critical role in the tunneling in the Himalayas.